Knowledge and prevention of hepatitis among secondary school students in Port Harcourt metropolis of Rivers State - Onwurah, C. C.; Kitoye, S. G.; Ikegulu, U. J.; Okoye, C. A.; Alozie, I. O.; Nnadi, C. C.; Egbegbotor A. (Journal of Research in Adult and Continuing Education, 2023)
This study examined the knowledge and attitude towards prevention of hepatitis among secondary school students in Port Harcourt metropolis of Rivers State. The study was guided by four research questions and three null hypotheses. Descriptive survey design was used and the population of the study consisted of 97,644 students. The sample of the study consisted of 400 students randomly selected using Taro Yamane Sampling Technique. The instrument for data collection was a 48 itemed questionnaire titled Knowledge and prevention of Hepatitis among Secondary School Students (KPHSSS). A reliability coefficient of .76 was obtained using Pearson Product Moment Correlation Coefficient which showed a positive correlation.  Data collected was analysed using Statistical Products for Service Solution (SPSS) version 23.0. Descriptive statistical tool was used to answer questions on demographic information while regression models were used to determine the relationship between variables. The results showed that the secondary school students have high knowledge of prevention of hepatitis, the students with middle parents’ socio-economic status have high knowledge of prevention of hepatitis, and the students with low parents’ socio-economic status also have high knowledge of prevention of hepatitis. Both male and female students have high knowledge of prevention of hepatitis, The Christian students, Muslims, as well as Traditional religion students also have high knowledge of prevention of hepatitis. Based on the findings of the study, it was recommended that government through the ministry of health should organize national campaign and enlightenment programme to promote awareness of hepatitis viral infections and other forms of infectious disease. Awareness should be made for compulsory immunization programme for students in secondary schools to be vaccinated against infectious diseases (hepatitis inclusive) in order to minimize the rate of spread in the population. The Ministry of Education should carryout routine immunization HBV screening among students to improve their knowledge towards prevention of hepatitis and also religious institutions should educate their members on the importance of prevention of infectious diseases.
Keywords: Hepatitis; Knowledge; Prevention; Infectious